Production of meat of rabbit, an alternative for the cooperative sector palmero to inclination of a project of municipal initiative of local development - Raúl Rosales Guzmán; Nigdalys Figueroa Sierra; Dania María Crespo Álvarez; Miladys Garrido Cervera (Cooperativismo y Desarrollo, 2015)
The present article contains an analysis on the possibilities offered by the cooperative sector in La Palma, which is supported by the local development initiative of breeding rabbits. This activity can be easily carried out with minimal cost and effort, and is supported by a tradition in the local population, mainly in the private sector. The proposal will allow the production of rabbit meat in order to ease the difficult situation regarding meat supply; constitute the fundamental problem of how to incorporate research conducted the cooperative sector in La Palma to development projects municipal initiative?